Nanosheet-Assembled MnO2-Integrated Electrode Based on the Low-Temperature and Green Chemical Route - Xiaoli Wang; Yin Wang; Xinyu Zhao (Crystals, 2022)
The development of superior electrochemical energy-storage devices designed through a facile, cost-efficient, and green synthesis technique is the key to addressing the intermittent nature of renewable energy sources such as solar and wind energy. In our present work, we design a simple, surfactant-free, and low-temperature chemical strategy to prepare novel integrated, MnO2 composite electrodes with two-dimensional (2D) nanosheet film directly supported on three-dimensional (3D) conductive nickel foam. Benefiting from the specific 2D nanosheet architecture to provide a large interfacial contact area and highly conductive metal scaffolds to facilitate fast electron transfer, the novel nanosheet-assembled MnO2-integrated electrodes exhibit higher specific capacitance of 446 F g−1 at the current density of 1 A g−1 compared with nanostructured MnO2 and commercial MnO2 powder electrodes. More importantly, the as-synthesized devices are able to achieve an outstanding cycling performance of 95% retention after 3000 cycles. The present work, which is based on the low-temperature chemical route to deposit active materials on the conductive substrate, provides new insights into designing a binder-free supercapacitor system to improve the specific capacitance, cycling, and rate performance as next-generation, energy-storage devices.